Is there any significance of lung cancer histology to compared the diagnostic accuracies of 18F-FDG-PET/CT and 99mTc-MDP BS for the detection of bone metastases in advanced NSCLC? - Inal, Ali; Kaplan, Muhammed Ali; Kucukoner, Mehmet; UrakcI, Zuhat; Dostbi, Zeki; Komek, Hail; Onder, Hakan; Tasdemir, Bekir; Isikdogan, Abdurrahman (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: Bone scintigraphy (BS) and fluorine-18 deoxyglucose positron emission tomography computed tomography ( 18 F-FDG-PET/CT) are widely used for the detection of bone involvement. The optimal imaging modality for the detection of bone metastases in histological subgroups of non-small cell lung cancer (NSCLC) remains ambiguous. The aim of this study was to compare the efficacy of 18 F-FDG-PET/C and 99m Tc-methylene diphosphonate ( 99m Tc-MDP) BS in the detection of bone metastases of patients in NSCLC. Specifically, we compared the diagnostic accuracies of these imaging techniques evaluating bone metastasis in histological subgroups of NSCLC. Material and methods: Fifty-three patients with advanced NSCLC, who had undergone both 18 F-FDG-PET/CT and BS and were eventually diagnosed as having bone metastasis, were enrolled in this retrospective study. Results : The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of 18 F-FDG-PET/CT and BS were 90.4%, 99.4%, 98.1%, 96.6%, 97.0% and 84.6%, 93.1%, 82.5%, 93.2, 90.8%, respectively. The κ statistics were calculated for 18 F-FDG-PET/CT and BS. The κ-value was 0.67 between 18 F-FDG-PET/CT and BS in all patients. On the other hand, the κ-value was 0.65 in adenocarcinoma, and 0.61 in squamous cell carcinoma between 18 F-FDG-PET/CT and BS. The κ-values suggested excellent agre-ement between all patients and histological subgroups of NSCLC. Conclusions : 18 F-FDG-PET/CT was morefavorable than BS in the screening of metastatic bone lesions, but the trend did not reach statistical significance in all patients and histological subgroups of NSCLC. Our results need to be validated in prospective and larger study clinical trials to further clarify this topic.